PhyOnto : An Ontology based Framework for Educational Physics Units and Measurements - Catherine Seng Jing, Hii; Chih How, Bong (Foundation of Computer Science (FCS), NY, USA, 2025)
The study of physics plays a fundamental role in understanding the natural world and its complex phenomena. To support accurate representation and computation of physics knowledge, digital ontologies have been developed. This paper presents a comprehensive physics ontology, PhyOnto, which captures domain knowledge related to units and measurement tools – critical elements in physics education and calculation. The ontology is constructed using the Web Ontology Language (OWL) within Protégé, following the “101 method” for ontology development. A series of rigorous evaluations, including taxonomy assessment, competency question validation, and content review, were conducted to establish its reliability and completeness. PhyOnto demonstrates strong potential in supporting physics education and questionanswering systems by enabling structured knowledge representation for calculation-based reasoning.